O Espaço Ficcional em Contos de Aníbal Machado - Lacerda, Andréa Maria de Araújo (2013)
Reading the academic papers about Aníbal Machado`s work, we noticed that space, although it is an important narrative element, once, for many times, it acts in the stories either influencing on the character`s actions and attitude or modifying its way of being or living, has not been studied enough. Therefore, this work has the aim to investigate, with more acuity, the fictional space in the tales of this writer, born in the state of Minas Gerais. For that, we analyzed Tati, a garota , "O telegrama de Ataxerxes" and "Viagem aos seios de Duília" stories, present in the book A morte da porta-estandarte e Tati, a garota e outras histórias (1976), which physical and social spaces, especially the city ones, play important part on the characters composition, propelling them to dislocate and live themselves, each in their own way, certain level of loneliness. Topoanalysis is our theoretical perspective, defended by Gaston Bachelard (2003), but amplified by Ozíris Borges Filho (2007). To justify our research, besides such authors contribution, we resorted to the Osman Lins (1976), Yi-fu Tuan s and Mikhail Bakhtin s insighful reflexions on space as analytical category. However, once the analyzed narratives took place preponderantly in Rio de Janeiro, we found necessary as well to introduce reflections both about city and about the capital carioca. Thus, on this topic, we consider Raquel Rolnik s (2012), Marshall Berman s (2007), Renato Cordeiro Gomes (2008), Nicolau Sevcenko s (1985), Brito Broca s reflections (2005), among other writers.